Effectiveness of Foreign Refugee Handling Services by Kupang Regional Government with the International Organization for Migration (IOM) - Ni Putu Tirka Widanti; Charles Fernandes (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2022)
This study aims to analyze the effectiveness of the service for handling the refugee from abroad in Kupang by the Regional Government of Kupang in collaboration with IOM after the delivery from the Kupang Immigration Detention Center and to examine the factors that cause the ineffectiveness of the foreign refugee handling services. This study uses qualitative research approach that focuses on analyzing the services for handling refugees from abroad in Kupang based on the concept of good service characteristics. The study found that the implementation of services for handling refugees from abroad in Kupang has not been effective due to: lack of participation by the Kupang Regional Government, lack of maintenance in the facilities and infrastructure in the shelter, lack of human resources officers at the shelter, local government feels not responsible for handling refugees, health services are less responsive, language barriers, Kupang local government does not have a database of refugees from abroad, lack of knowledge on refugee status and human rights enforcement by immigration officers, the reactive attitude of the refugees that reduce the trust of the Kupang Rudenim. In conclusion, the effectiveness of refugees from abroad handling services in Kupang which is managed by the Kupang Regional Government in collaboration with International Organization for Migration (IOM) is still not optimal if judged based on good service indicators.